3D bioprinting of organs: revolutionizing transplant medicine and personalized healthcare - Muhammad Abdul Rafay; Alisha Hafeez; Umaiymah Irfan (Journal of the Pakistan Medical Association, 2026)
Dear Madam, 3D organ printing is changing transplant medicine and personalized healthcare by producing functional, lifelike tissues from living cells and biomaterials. Using computer-assisted designs and layer-by-layer bio-ink printing, it creates delicate tissue structures that resemble real organs. It creates more spatial control, scalability, and personalization than conventional tissue engineering, which lacks complexity and accuracy in microenvironments. This accelerates the production of essential organs, including the heart, liver, and kidneys. With all the ongoing advancements, this could help to alleviate organ shortages and improve tailored therapies for individual patients. 3D bioprinting revolutionizes transplant medicine which eliminates donor dependence and minimizes the risk of transplant rejection by creating organs tailored to each patient individually. According to research conducted in 2019, approximately 153,000 organ transplants were completed globally using traditional methods; demand continued to exceed supply, highlighting a serious transplant problem. It closes this essential gap by providing patient-specific organs (1). 3D bioprinting has the potential to reduce global organ shortages. In 2016, 122,071 patients in the United States were on the transplant waiting list, with more than half waiting over two years. It can reduce waiting times for patients and also it can make mass production of organs possible (2). Over the last 2 decades, 3D bioprinting has shown great possibility in transforming healthcare through advancements in personalized medicine. Using these bio printed patient-specific tissues and multi-organ chips to accurately predict drug responses, toxicity, and metabolism, it allows for safer, more effective treatments tailored to each individual’s unique genetic and physiological makeup (3). 3D bioprinting turns out to have a significant impact on cancer therapy by producing precise tumor models that replicate the complicated tumor microenvironment. Hence it improves drug testing, understanding cancer biology, and monitoring tumor progression and provides superior insights into chemoresistance, cell interactions, and tumor behavior than typical cancer treatment regimens (4). Even with this much progress, 3D bioprinting technology still faces several challenges. For example, a better understanding of cell matrix interaction is needed for safer transplants and many more. In addition, 4D bioprinting that uses smart hydrogels provides an opportunity to advance 3D bioprinting and improve healthcare. To summarize, 3D bioprinting is an intriguing concept in the field of regenerative medicine and tissue engineering. It is resetting standards in healthcare for treatments with targeted therapies based on patient-derived tissues and tumor models and has the potential to revolutionize drug testing, cancer therapy and organ transplantations.